Proceedings of the Boston Area Colloquium in Ancient Philosophy 2006 . (Proceedings of the Boston Area Colloquium in Ancient Philosophy, 2007)
This volume contains papers and commentaries presented to the Boston Area Colloquium in Ancient Philosophy during the academic year 2005-6. Of the two colloquia on Neoplatonism, one offers a phenomenological reading of Plotinus on the Intellect, while the other discusses consciousness and introspection in Plotinus and Augustine. With regard to Aristotle's ethics, one colloquium discusses the influence of force and compulsion on human action, while another examines his views on the relationship between external goods and happiness. Two other colloquia are devoted to Aristotle's Metaphysics, discussing form and function in relation to his theory of substance, as well as his paradigmatism. Finally, a single colloquium on Plato discusses the happiness of philosopher-kings in the Republic.